Benefits and harms of hemithyroidectomy, total or near‐total thyroidectomy in 1–4 cm differentiated thyroid cancer. (30th May 2021) - Xu, Yang; Huang, Kunzhai; Huang, Peiyin; Ke, Najun; Zeng, Jinyang; Wang, Liying; Liu, Changqin; Shi, Xiulin; Guo, Fangting; Su, Lijia; Lin, Mingzhu; Li, Xuejun; et al.
Abstract: Objective: For 1–4 cm differentiated thyroid cancer (DTC), current ATA guideline recommended hemithyroidectomy (HT) as an acceptable alternative initial procedure to total or near‐total thyroidectomy (TT). The aim of this study was to evaluate benefits and harms of HT, TT in 1–4 cm DTC. Design: Retrospective cohort study. Patients: DTC patients aged 18 years or older who underwent initial thyroidectomy in a tertiary medical centre were included from January 2008 to July 2018. Measurements: The structural persistent/recurrent disease, reoperation rates and surgical complications were compared using Cox proportional regression and logistic regression. Propensity score matching was performed to adjust for related clinicopathological variables. Results: Among 1824 DTC patients, 795 patients sized 1–4 cm were included. A total of 286 patients underwent HT and 509 patients underwent TT. In the matched analysis, no significant difference in disease‐free survival (DFS) between HT and TT was observed during the median follow‐up period of 56.5 months (hazard ratio [HR] 0.86; 95% CI, 0.37–2.00; p  = .733). The difference in DFS between two groups was consistent regardless of age, sex, tumour size, follow‐up duration. Meanwhile, HT was associated with a decreased risk of surgical complications (odds ratio [OR] 0.47, 95% CI 0.31–0.71, p  < .001), as well as lower proportion of levothyroxine replacement ( p  = .007). Two cases in HT group received reoperation. Further multivariate analysis showed surgical procedure was not associated with structural persistence/recurrence (HR 0.68; 95%CI, 0.29–1.58, p  = .367). Conclusions: For patients with 1–4 cm DTC without clinical evidence of lymph node metastasis or extrathyroidal extension, HT was associated with lower risk of surgical complications than TT while provided similar benefits as TT.